Investigation of Electrode Electrochemical Reactions in CH3NH3PbBr3 Perovskite Single‐Crystal Field‐Effect Transistors. Issue 35 (11th July 2019) - Wang, Junzhan; Senanayak, Satyaprasad P.; Liu, Jie; Hu, Yuanyuan; Shi, Yanjun; Li, Zelun; Zhang, Caixin; Yang, Bingyan; Jiang, Longfeng; Di, Dawei; Ievlev, Anton V.; Ovchinnikova, Olga S.; et al.
Abstract: Optoelectronic devices based on metal halide perovskites, including solar cells and light‐emitting diodes, have attracted tremendous research attention globally in the last decade. Due to their potential to achieve high carrier mobilities, organic–inorganic hybrid perovskite materials can enable high‐performance, solution‐processed field‐effect transistors (FETs) for next‐generation, low‐cost, flexible electronic circuits and displays. However, the performance of perovskite FETs is hampered predominantly by device instabilities, whose origin remains poorly understood. Here, perovskite single‐crystal FETs based on methylammonium lead bromide are studied and device instabilities due to electrochemical reactions at the interface between the perovskite and gold source–drain top contacts are investigated. Despite forming the contacts by a gentle, soft lamination method, evidence is found that even at such "ideal" interfaces, a defective, intermixed layer is formed at the interface upon biasing of the device. Using a bottom‐contact, bottom‐gate architecture, it is shown that it is possible to minimize such a reaction through a chemical modification of the electrodes, and this enables fabrication of perovskite single‐crystal FETs with high mobility of up to ≈15 cm 2 V −1 s −1 at 80 K. This work addresses one of the key challenges toward the realization of high‐performance solution‐processed perovskite FETs. Abstract : Electrochemical reaction at the interface between the perovskite and a nominally inert gold metal electrode during device operation is investigated in perovskite single‐crystal field‐effect transistors (FETs). Such interfacial reactions can be minimized through suitable chemical modification of electrodes, allowing the demonstration of single‐crystal perovskite FETs with mobilities of up to ≈15 cm 2 V −1 s −1 at low temperature.